(3GdUfGYJjf (B: (3GdcJGHI hGdTYQs - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s ((3eMeO aVd Gddg GdWjH GdTGei s)
(3ChdgG (B:s
(3GdMeO ddg hdi cd fYeI hUdi Gddg Ydi fHjg s
(3BNQgG (B:s
(3Ydi Cf gPG GdcJGH bO LeY ef afhf eG jMJGL Edjg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1082s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs